1978
DOI: 10.1159/000114931
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vincamine on the Regional Cerebral Blood Flow in Man

Abstract: The cerebral hemodynamic action of Vincamine is measured in 17 patients with primary or secondary cerebral circulation disorders, by use of the multiregional 133Xe clearance technique. The statistical analysis of the results justifies the grouping of all the cases and the distinction between reference, ischemic and hyperemic zones by determining for each subject a range of + or –15% of his own mean regional cerebral blood flow. The drug, in a single injection in the internal carotid artery, shows a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1981
1981
2005
2005

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The blood flow recorded in the ischemic areas and the average blood flow in the surrounding brain during induced hypertension is also shown in table 4.…”
Section: Rcbf Recorded Over Ischemic Infarctsmentioning
confidence: 99%
See 1 more Smart Citation
“…The blood flow recorded in the ischemic areas and the average blood flow in the surrounding brain during induced hypertension is also shown in table 4.…”
Section: Rcbf Recorded Over Ischemic Infarctsmentioning
confidence: 99%
“…Our own group uses a fast-rotating single photon emission tomograph for measuring the wash-out of inhaled lw xenon in 3 slices of the brain simultaneously. * 4 Both methods are primarily used to study patients with focal cerebral ischemia, in particular, patients in whom reconstructive vascular surgery is under consideration. However, while these tomographic approaches avoid the look-through phenomenon, Compton scatter interference cannot be entirely avoided.…”
Section: Comments On the Low Rcbf Values Recorded Orer Infarctsmentioning
confidence: 99%
“…For example, Depresseux (1978) has shown that the intracarotid administration of vincamine increases the blood flow in the ischaemic foci and reduces blood flow in the hyperaemic regions of cerebrovascular disease. This "inverse steal phenomenon" has been observed with vincamine and a few related agents in other clinical studies (Herrschaft, 1977;Heiss and Podreka, 1978).…”
Section: Use Of Vasoactive Drugs In Focal Cerebral Ischaemiamentioning
confidence: 99%